The charge of c in animal behavior: a philosophical analysis - Dikmelik, Ediz. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2009., 2009)
Anthropomorphism has been a common criticism of the attempts to interpret nonhuman animals as subjects of psychological attributes. It is held that anthropomorphism is a fallacy which must be avoided to do good science. However, far from being a well defined and properly understood fallacy, anthropomorphism is a term which is used casually as a criticism. There seems to be a charge of anthropomorphism, rather than a fallacy of anthropomorphism. In this thesis, I examine the charge of anthropomorphism in an attempt to understand what it means and whether it is a valid criticism. First, I explicate the nature of the error implicated in the charge of anthropomorphism. Second, I focus on two different forms this charge can take in the context of animal behavior and bring to the fore the presuppositions which ground these charges. A thorough evaluation of these presuppositions shows that they cannot provide a solid foundation for the charge of anthropomorphism. Third, I apply the charge of anthropomorphism to a real study from cognitive ethology as an example and show that it fails to be a serious criticism. I conclude that in the context of animal behavior, anthropomorphism does not refer to a serious fallacy as usually supposed, and that it obscures real questions that arise in the study of nonhuman animal mentality.
Keywords: Anthropomorphism.